Curcumin aggravates CNS pathology in experimental systemic lupus erythematosus. - Foxley, S; Zamora, M; Hack, B; Alexander, R; Roman, B; Quigg, R; Alexander, J (2013)
Complement activation and inflammation are key disease features of systemic lupus erythematosus. Curcumin is an anti-inflammatory agent that inhibits the complement cascade. Therefore, we hypothesized that curcumin will be protective in CNS lupus. To assess the effect of curcumin on CNS-lupus, MRL/lpr mice were used. Brain MRI showed that curcumin (30mg/kg body wt. i.p. from 12-20 weeks) worsened regional brain atrophy. The volumes of the lateral and third ventricles are significantly increased (150%-213% and 107%-140%, without and with treatment respectively compared to MRL+/+ controls). The hippocampus was reduced further (83%-81%) by curcumin treatment. In line with increased brain atrophy, there were edematous cells (41% increase in cell size in MRL/lpr compared to MRL+/+ mice. The cell size was further increased by 28% when treated with curcumin; p<0.02) in the cortex. In line with increased atrophy and edema, there was a significant increase (p<0.02) in the mRNA and protein expression of the water channel protein, aquaporin 4 in these mice. The increase in the matrix proteins, glial fibrillary acidic protein and vimentin in lupus mice in the hippocampus was prevented by curcumin. Curcumin increased IgG deposits and decreased C3 deposits in brain with a corresponding increase in immune complexes and decrease in C3 concentration (by 60% in MRL/lpr mice Vs. MRL+/+ mice and a further 26% decrease when treated with curcumin) in circulation. Decrease in C3 could alter the transport of immune complexes leading to an increase in IgG deposits which could induce inflammatory pathways thereby leading to worsening of the disease. The neurological outcome as measured by maze performance indicates that the curcumin treated mice performed poorly compared to the untreated counterparts. Our results for the first time provide evidence that at the dose used in this study, curcumin aggravates some CNS disease manifestations in experimental lupus brain. Therefore, until a safe dose range is established by additional studies, and the validity of the findings is determined in human patients, caution may be warranted in the use of curcumin, even as adjuvant therapy for CNS lupus.